“RULE BY LAW” ECONOMIC INSTITUTION IS THE BASIC SYSTEM OF VALUES ENHANCING THE DEVELOPMENT PROCESS OF THE MARKET ECONOMY TOWARDS SOCIALIZM INVIETNAM - Nguyen, Thuong Lang (ĐHQGHN, 2015)
Vietnam has been a membership of WTO and being in a process of wide and deep integration into the global economy. In case of that all economic transactions or the transactions conveing the commercial nature become popular, construct the infrastucture of the society and are consistent with the international rule-liberalization, transparency and fairness, the improving the “rule by law” economic institution becomes a central issue of the process shifting from a centrally planned command economy towards an economy directed by market mechanism. By nature, such this process is one basically transforming from a system of values of a centrlally planned economy towards a system of values of a market one that is at the highest level reflected in the terms of liberalization, transparency and fairness of its trading system. Simultaneously, if the economic institution would run in an appropriate way with legislation, it would represent the consistency between the infrastructure and superstructure. Such this consitency, in its turn, would push the society operate in the right direction towards the proposed target and take effectively the global driving force to serve the course of development.